Cross-Talk between Metabolism and Reproduction: The Role of POMC and SF1 Neurons - Xu, Yong; Faulkner, Latric; Hill, Jennifer W. (Frontiers in Endocrinology, 2012)
Energy homeostasis and reproduction need to be tightly coordinated. The mechanisms for this coordinated control are not fully understood. Two subsets of hypothalamic neurons, namely pro-opiomelanocortin (POMC) neurons in the arcuate nucleus and steroidogenic factor-1 (SF-1) neurons in the ventromedial hypothalamic nucleus, are emerging as critical nodes where metabolic and reproductive signals communicate. This notion is supported by recent genetic studies showing that disruptions of metabolic signals (e.g. leptin and insulin) or reproductive signals (e.g. estrogen) in these neurons lead to impaired regulation of both energy homeostasis and fertility.